Soluble Thrombomodulin and Major Orthopedic Surgery - Irina P. Antropova; Boris G. Yushkov; Evgeny Kobrinsky; Anatoliy N. Varaksin (International Journal of Biomedicine, 2016)
Background: A high level of soluble thrombomodulin (sTM) is associated with a lower risk of thrombosis but can cause severe bleeding after operations. Deep vein thrombosis (DVT) and blood loss are serious threats after orthopedic surgery. The aim of our pilot study was to evaluate the effect of the preoperative level of sTM on coagulation and inflammation as well as the blood loss and the development of symptomatic DVT after total large joint replacement. Methods and Results: In all patients (n=50) who underwent total hip or knee replacement, sTM, PrC, D-dimer, vWF, CRP, and platelets were determined before and after the operation. According to the preoperative sTM level, patients were divided into 2 groups: the thrombomodulin low (TML) group (n=25) and thrombomodulin high (TMH) group (n=25). The concentration of sTM was 4.4 [3.4, 4.7] ng/ml in the TML-group and 8.7[7.3, 10.6] ng/ml in the TMH-group. After surgery, D-dimer, vWF, platelet count and CRP were higher and total blood loss was lower in the TML group. In the TML-group, a symptomatic DVT was detected in 3(12%) patients; in the TMH-group, a symptomatic DVT was identified only in 1(4%) case. Conclusion: These findings support the important role of sTM in coagulation, inflammation, bleeding, and presumably in venous thrombosis after major orthopedic surgery.